Jason Antrosio & Rudi Colloredo-Mansfield: Fast, Easy, and In Cash. Artisan Hardship and Hope in the Global Economy - Rasmussen, Mattias Borg (Tidsskriftet Antropologi, 2019)
Jason Antrosio & Rudi Colloredo-Mansfield: Fast, Easy, and In Cash. Artisan Hardship and Hope in the Global Economy Anmeldes af Mattias Borg Rasmussen